2022
DOI: 10.1021/jacs.2c06688
|View full text |Cite
|
Sign up to set email alerts
|

Chloride-Mediated Alkene Activation Drives Enantioselective Thiourea and Hydrogen Chloride Co-Catalyzed Prins Cyclizations

Abstract: The mechanism of chiral hydrogen-bond donor (HBD) and hydrogen chloride (HCl) co-catalyzed Prins cyclizations was analyzed through a combination of experimental and computational methods and revealed to involve an unexpected and previously unrecognized mode of alkene activation. Kinetic and spectroscopic studies support the participation of a catalytically active HCl•HBD complex that displays reduced Brønsted acidity relative to HCl alone. Nevertheless, rate acceleration relative to the HCl-catalyzed backgroun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 80 publications
0
7
0
Order By: Relevance
“…Furthermore, we did not observe any nonlinear effects in this reaction (see details in the Supporting Information). Combined with the above titration study, this observation may suggest that a 2H-binding mode between the catalyst and chloride (i.e., TU4 /Cl – = 1:1) in the enantiodetermining transition state, which is also consistent with the known chloride/thiourea interaction in the literature . Unfortunately, the addition of the sulfonium substrate to the catalyst-chloride adduct did not permit the observation of the chiral ion pair intermediate.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we did not observe any nonlinear effects in this reaction (see details in the Supporting Information). Combined with the above titration study, this observation may suggest that a 2H-binding mode between the catalyst and chloride (i.e., TU4 /Cl – = 1:1) in the enantiodetermining transition state, which is also consistent with the known chloride/thiourea interaction in the literature . Unfortunately, the addition of the sulfonium substrate to the catalyst-chloride adduct did not permit the observation of the chiral ion pair intermediate.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Based on the above results and the related known catalytic systems with chiral thioureas, , a possible reaction pathway is proposed (Figure ). Due to the favorable affinity to chloride, the thiourea catalyst abstracts a chloride anion in the aqueous phase by anion binding.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Our studies on the cocatalytic effect of HCl and chiral HBDs in protio-semipinacol rearrangements were initiated using phenyl-substituted vinylic cyclopropyl alcohol 1a as a model substrate. Drawing on prior work on the activation of aldehydes toward Prins cyclization reactions, we found that thiourea derivative 2a (10 mol %) and an ethereal solution of hydrochloric acid (5 mol %) in toluene promoted the isomerization of 1a to the ring-expanded cyclobutanone 3a in 97% yield with 83% ee (Table , entry 1). Extensive variation of the structure and nature of the chiral dual HBD cocatalyst revealed the best results for compounds with the general structure in 2 but a surprisingly flat enantioselectivity landscape within that family of catalysts (see SI sections 2.3 and 13).…”
mentioning
confidence: 87%
“…This strategy offers the potential to access chiral variants of Brønsted acids possessing an essentially unlimited range of acidities. To this end, chiral dual-hydrogen-bond donors (HBDs) have been utilized to impart enantioselectivity in transformations of imines and carbonyl compounds promoted by sulfonic acids or HCl (Figure A). , We sought to determine whether this cocatalysis concept could be extended to reaction of olefins that upon protonation generate carbocationic intermediates lacking heteroatom stabilization, focusing on the specific case of protio-semipinacol 1,2-ring-expansion processes (Figure B).…”
mentioning
confidence: 99%
“…Due to the lack of structural commonality among nucleophile and electrophile reaction components beyond classifying bond-forming electrophilic and nucleophilic atoms, we deployed two-dimensional (2D) parameters typically used in quantitative structure activity relationship (QSAR)-based analyses to supplement the parameter library . Each of these four HBD-catalyzed reactions involves the conversion of the electrophile into a cationic intermediate. ,, To capture the electropositive nature of the substrate in the proposed transition state, all computational treatment of the electrophiles were in the charged state. …”
Section: Computational Workflowmentioning
confidence: 99%